PENGARUH PENGETAHUAN, PERSEPSI KEMUDAHAN DAN PERSEPSI MANFAAT TERHADAP INTENSI PENGGUNAAN QRIS SEBAGAI METODE PEMBAYARAN DIGITAL (Studi Pada Mahasiswa Universitas Mercu Buana Meruya) - Ramanda, Malia Nastia; Parmariza, Yennida (Universitas Mercu Buana, 2024)
This study aims to analyze the influence of knowledge, perceived convenience, and perceived usefulness on the intention to use QRIS among Mercu Buana Meruya University students. The population studied were students who knew QRIS and had never used QRIS as a digital payment method, with a sampling technique, namely purposive sampling. The number of samples was calculated using the Hair formula, namely with a result of 110 respondents. The data analysis method used is the Partial Least Square Technique using SmartPLS statistical software version 4.0, with the research instrument being a questionnaire. The results of this research show that knowledge, perceived convenience and perceived benefits have a positive and significant effect on intentions to use QRIS as a digital payment method.